Policy Directives for Sustainable Settlement Development at Flood Hazard Zone in Limapuluh Kota District West Sumatera Province, Indonesia - Umar, Iswandi (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The flood disaster has caused much harm to human life. Efforts to reduce the losses incurred by the policy directed the development of disaster-based residential areas based. The purpose of determining the direction of the policy of settlement development in the area of flood hazard in Limapuluh Kota District. To determine policy direction using AHP approach by involving 25 experts from related institutions. To determine the sustainability of development using the MDS approach. The result of policy analysis of the development of settlement area in the flood hazard area shows that there are three alternatives, namely a) disaster education; b) increased socialization in the flood hazard zone, and c) disaster-based space planning. In addition, the analysis of the sustainability of the development of residential areas shows that the institutional and legal dimensions are still low. Therefore, it is necessary to have the firmness and consistency of the government in spatial planning.